Insights into the Nature of Formate Species in the Decomposition and Reaction of Methanol over Cerium Oxide Surfaces: A Combined Infrared Spectroscopy and Density Functional Theory Study - Lustemberg, Pablo German (2015)
Formation of formate species on oxide surfaces plays a role in reactions for hydrogenproduction such as the water-gas shift, and the steam reforming of alcohols. It has beensuggested that bridge formates are the most common and stable configuration on metaloxides. Ceria-based catalysts are important for these reactions where ceria is a ?noninnocent?support. In this work, the nature of the formate species that are formedduring decomposition and reaction of methanol on ceria surfaces have been studiedusing a combination of infrared temperature programmed surface reaction (TPSR-IR)on a real powder catalyst support, and density functional theory (DFT) together withstatistical thermodynamics for model CeO2(111) surfaces. The influence of surfaceoxygen vacancies, hydroxyl groups, and water has been considered. Three differentformate species have been identified (450−550 K). Initially, formates are adsorbed onthe oxidized surface that is gradually hydroxylated by the release of hydrogen frommethoxy groups (> 500 K), which leads to a partially reduced surface. On the formerone kind of species is observed, whereas on the latter the other two kinds appeared. Weprovide computational evidence that the bonding is only initially of the bridge type, butbecomes of the monodentate type, as the surface concentration of hydroxyl groups rises.The calculated frequencies of the O−C−O symmetric and asymmetric stretching modesfor the three structures are in good agreement with those experimentally observed. Theexistence of monodentate species is discussed in terms of a stabilizing effect of hydrogenbonds. The combined experimental and theoretical results on real and model systems,respectively, thus provide important insights on the reaction of methanol on ceriasurfaces.